2018
DOI: 10.12927/hcq.2018.25637
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Together Research and Quality Improvement: The Saskatchewan Approach

Abstract: Improving health and health services requires both better knowledge (a key function of research) and better action to adapt and use what is already known (quality improvement). However, organizational and cultural divides between academic research institutions and health system organizations too often result in missed opportunities to integrate research and improvement. The Saskatchewan Health Quality Council's experience and relationships, from linking research, quality improvement and patient engagement in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Cette réalité a d'importantes répercussions politiques sur l'avenir de l'engagement des patients et des citoyens au Canada, car elle exige un leadership à tous les niveaux du système de santé, dont une collaboration des gouvernements national et provinciaux avec les établissements et responsables locaux des soins de santé. L'exemple de Teare et Keller (2018), en Saskatchewan, illustre un autre type de carrefour d'engagement (au niveau provincial), qui crée une infrastructure commune entre deux domaines d'engagement (la recherche et l'amélioration de la qualité) afin de faciliter l'apprentissage mutuel et le partage de ressources. En intégrant son unité de soutien à la recherche axée sur le patient (dotée d'un mandat consacré à la recherche sur l'engagement des patients) au sein du Saskatchewan Health Quality Council (qui possède déjà une expertise en matière d'engagement des patients à l'amélioration de la qualité), la Saskatchewan a exploité des ressources existantes (p. ex.…”
Section: Resultsunclassified
“…Cette réalité a d'importantes répercussions politiques sur l'avenir de l'engagement des patients et des citoyens au Canada, car elle exige un leadership à tous les niveaux du système de santé, dont une collaboration des gouvernements national et provinciaux avec les établissements et responsables locaux des soins de santé. L'exemple de Teare et Keller (2018), en Saskatchewan, illustre un autre type de carrefour d'engagement (au niveau provincial), qui crée une infrastructure commune entre deux domaines d'engagement (la recherche et l'amélioration de la qualité) afin de faciliter l'apprentissage mutuel et le partage de ressources. En intégrant son unité de soutien à la recherche axée sur le patient (dotée d'un mandat consacré à la recherche sur l'engagement des patients) au sein du Saskatchewan Health Quality Council (qui possède déjà une expertise en matière d'engagement des patients à l'amélioration de la qualité), la Saskatchewan a exploité des ressources existantes (p. ex.…”
Section: Resultsunclassified
“…Social learning articles de-emphasized organizational structures or boundaries and instead highlighted transformative group processes with all relevant knowledge holders [55,58]. Learning health system documents were the only ones not to consider transformation of underlying group norms, assumptions or behaviour as part of the de nitions they used, though some did acknowledge the importance of human interactions for learning and knowledge dissemination [57,59,60].…”
Section: Characteristics Of Included Documentsmentioning
confidence: 99%
“…Learning from, and learning with, community Ten (24%) texts suggested that organizational learning could be done with community [22,56,57,60,74,77,[80][81][82][83]. Nine (21%) texts suggested that organizations could learn both from and with the communities they served [52,55,59,64,78,79,[84][85][86].…”
Section: Conceptualizing Communitymentioning
confidence: 99%
See 2 more Smart Citations